1996
DOI: 10.1002/pssa.2211550205
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of Cu, Ni, and Fe on Frank-Type Partial Dislocations in Czochralski-Grown Silicon

Abstract: The segregation behavior of metallic impurities, Cu, Ni, and Fe on Frank‐type partial dislocations in Czochalski‐grown silicon depends not only on the species of impurities, but also significantly on the cooling rate of the specimen after contamination. In slowly cooled specimens, Cu develops precipitate colonies in the region away from Frank partials and does not decorate them even on an atomic scale, while Ni decorates Frank partials weakly. A high density of Cu or Ni precipitates is observed on Frank partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In contrast, iron silicide precipitates have large misfits to the silicon matrix and hence, their formation is hindered by large nucleation energy barriers. Fe impurity atoms precipitate only heterogeneously 8 and can be detected as fine distributions along dislocation cores by EBIC 38. Thus, either Fe silicide precipitates too small to be detected by TEM formed along structural defects, or large elastic forces at RT impeded the formation of Fe silicide precipitates completely.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, iron silicide precipitates have large misfits to the silicon matrix and hence, their formation is hindered by large nucleation energy barriers. Fe impurity atoms precipitate only heterogeneously 8 and can be detected as fine distributions along dislocation cores by EBIC 38. Thus, either Fe silicide precipitates too small to be detected by TEM formed along structural defects, or large elastic forces at RT impeded the formation of Fe silicide precipitates completely.…”
Section: Discussionmentioning
confidence: 99%
“…However, detailed studies revealed that Cu does not decorate all types of extended defects, but prefers stacking faults, [78][79][80][81][82] grain boundaries, [83][84][85][86][87] and Frank-type partial dislocations. [88][89][90] The effect of lattice strain and electrostatic effects on the precipitation behavior of Cu discussed above suggests that preferential Cu precipitation at certain types of defects may be associated with either their electrical charge ͑negatively charged defects will attract Cu͒, or with local strain fields around them ͑nucleation barrier for the formation of Cu-silicide precipitates will be reduced in the areas of tensile strain͒.…”
Section: ͓2͔mentioning
confidence: 99%
“…The behavior of copper precipitation in Cz-Si and the electrical properties of dislocation or grain boundaries contaminated with copper have been widely studied by many groups [7][8][9][10][11][12][13][14][15][16][17][18]. But up to now, few papers have been published about copper precipitation in cast multicrystalline silicon (mc-Si) [19,20].…”
Section: Introductionmentioning
confidence: 99%